Fertility, divorce and the future of children (Journal of Parents and Teachers, 2026)
Throughout its evolution, the European family faces various challenges and changes that affect both parents and children, altering emotional bonds, parental roles and the learning of values. This article proposes a reflection on educational, social and ethical-scientific alternatives for better adaptation to these transformations.
Keywords: Family, Evolution, Transformation, and Adaptation.